Nursing-led enhanced recovery bundled care in colorectal cancer surgery: a systematic review and meta-analysis - Pan, Wei; Yang, Yan-Ling; Che, Na; Li, Ying; Ma, Qian (Journal of Gastrointestinal Oncology, 2026)
Background: The protocols of Enhanced Recovery After Surgery (ERAS) have transformed the perioperative nursing care by decreasing surgical stress and shortening the recovery period because of multidisciplinary and evidence-based practice. The enhanced recovery bundled care (ERBC) emphasizes the core role of a nurse in aligning the ERAS components of patient education and early mobilization to pain management with which the surgical outcomes can be enhanced further. The purpose of this systematic review and meta-analysis was to assess and meta-analyses the effectiveness of nursing-led ERBC during the colorectal cancer surgical process in terms of main postoperative outcomes, such as the hospital length of stay (LOS), readmission rates, postoperative complications, and survival/prognosis in general.Methods: Following PRISMA 2020 guidance, we searched PubMed, Embase, Scopus, Web of Science, and Cochrane Library for studies published in the last 10 years evaluating nursing-led ERAS bundled care in colorectal cancer surgery. Two reviewers independently screened records, assessed full texts, and extracted data. A random effects meta-analysis was performed for outcomes reported with sufficient comparability across studies.Results: From 2,586 records identified, 13 studies were included. Across studies, nursing-led ERAS bundled care was associated with shorter LOS and earlier return of bowel function, with complication and readmission rates that were similar or lower than conventional pathways. Evidence for long-term oncologic outcomes was limited, but several cohort studies suggested improved survival with higher ERAS adherence.Conclusions: Nurse-led or nursing-coordinated ERAS bundled care was associated with improved short-term postoperative recovery in colorectal cancer surgery, including shorter hospital stay and lower complication and readmission rates, without evidence of increased short-term mortality. These findings support the potential value of structured nurse-coordinated perioperative pathways, although heterogeneity in the definition and reporting of nursing components limits causal inference. Further prospective multicenter studies are needed to operationalize nursing leadership, measure ERAS adherence reproducibly, and evaluate long-term oncologic and economic outcomes.